HUBUNGAN ANTARA KOMPETENSI PENYULUH DENGAN PARTISIPASI ANGGOTA DALAM KEGIATAN KELOMPOK TANI DI KECAMATAN BANYUDONO KABUPATEN BOYOLALI - Arip Wijianto (Universitas Sebelas Maret, 2010)
This research aim detects connection between extension agent competence with member participation in farmer that be farmer group member at district Banyudono regency Boyolali. Research sample is taken with technique multistage cluster random sampling as much as 50 person. Second research data that is extension agent competence and member participation in farmer group activity is gathered to pass inquiry formed instrument. Instrument validity is tested by using grain validity, while to detect reliabilities used internal consistency test with fomula alfa-cronbach. Furthermore data is analyzed with correlation technique. Analysis result in standard signifikansi 5% show that: found connection significant between extension agent competence with member participation in farmer group activity (rxy = 0,561 > rtab =0,279).